Keseimbangan Kehidupan-Kerja dan Kualitas Hidup pada Karyawan di Jawa Tengah saat Masa Pandemi COVID-19 - Nainggolan, Erida Yeussy; Wijono, Sutarto (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to determine the relationship between work-life balance and quality of life among employees in Central Java during the COVID-19 pandemic. The respondents in this study were 349 Central Java employees that were gathered by voluntary sampling. The measuring instrument used in this study was Fisher Work-life Balance Scale adapted by Gunawan, et al. (2019) with Crobach’s alpha coefficient of 0,877 and the Quality of life scale translated into Indonesian by the researcher herself based on the theory Flanagan Quality of Life (1978) with 0,850 of Cronbach’s alpha coefficient. From the Spearman Rho data analysis, the result showed (r = 0,281 ; p < 0,05) there is a correlation between work-life balance and the quality of life of Central Java employees during the COVID-19, so the hypothesis in this study is able to be accepted.